2007
DOI: 10.1186/1471-2105-8-218
|View full text |Cite
|
Sign up to set email alerts
|

Novel and simple transformation algorithm for combining microarray data sets

Abstract: Background: With microarray technology, variability in experimental environments such as RNA sources, microarray production, or the use of different platforms, can cause bias. Such systematic differences present a substantial obstacle to the analysis of microarray data, resulting in inconsistent and unreliable information. Therefore, one of the most pressing challenges in the field of microarray technology is how to integrate results from different microarray experiments or combine data sets prior to the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Several approaches have been proposed and are generally classified into two main categories: (1) integrate profiles from different studies into one dataset so that available analysis tools can be directly applied to the concatenated dataset or (2) analyze and interpret each dataset separately and subsequently compare the analysis (meta-analysis). 20–27 Since combining data across different platforms remains a serious challenge, meta-analysis approaches are gaining popularity 28,29 given the underlying hypothesis is that even though raw data may not be comparable, the results of the individual analyses are.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been proposed and are generally classified into two main categories: (1) integrate profiles from different studies into one dataset so that available analysis tools can be directly applied to the concatenated dataset or (2) analyze and interpret each dataset separately and subsequently compare the analysis (meta-analysis). 20–27 Since combining data across different platforms remains a serious challenge, meta-analysis approaches are gaining popularity 28,29 given the underlying hypothesis is that even though raw data may not be comparable, the results of the individual analyses are.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have concluded that there were differences between the results from these two types of data sets and the sensitivity to detect differential gene expression from microarray data sets using amplified RNA was also different compared to using total RNA [ 29 , 30 ]. It was also confirmed that systematic biases existed between these two data sets using unsupervised hierarchical cluster analysis [ 31 ].…”
Section: Methodsmentioning
confidence: 67%
“…By adopting a similar approach to Kim et al [ 36 ] we present a cluster plot in Figure 3 that shows a relationship between the three datasets before data integration. We find that if clustering of individual samples is done using relative gene expressions (i.e expressions of genes in HCV to normal tissue), the samples cluster according to each individual platform, indicating the presence of intra-study variability due to lab/platform effects.…”
Section: Resultsmentioning
confidence: 99%